PTU-088 Day case elective paracentesis. (June 2019) - Dix, Hannah; Cracknell, Miss Heather; Henry, Elaine; Barron, Morag
Abstract : Introduction: Increasing prevalence of chronic liver disease has caused demand for elective paracentesis in refractory ascites to exceed capacity in NHS Tayside, with patients diverting to acute care areas. Assessing the current elective care pathway has allowed us to develop the service in order to increase capacity, reduce pressures on unplanned care and reduce costs. Method: 12 weeks of prospective data were collected on patients receiving elective paracentesis. Recommendations made on analysis of this data (Excel) led to changes in the standard operating procedure and a further 6 weeks of prospective data collection closed the PDSA cycle. Results: In the initial data collection, 31 elective paracentesis' were completed on 15 individual patients. Drains were in situ for a median of 24 hours, necessitating an overnight stay. On average 10, 966ml of fluid were drained (range 4324ml – 19692ml). The rate of ascitic drainage plateaued at 8 hours, with an average, 74% (range 53%-100%) of total ascitic fluid drained at this point. From this we hypothesized that adequate drainage could be achieved with a day case procedure. During the second data collection, 27 elective paracentesis' were completed on 12 individual patients with drains in situ for 8 hours. On average 8, 123ml of fluid were drained (range 3903ml – 20996ml). If we extrapolate this data over 12weeks we could accommodate a 74% increase in capacity between study groups. 20% albumin replaced 4.5% to reduce volume infused, therefore reducing further time constraints on admission. On average 3 bottles of 4.5% albumin were used in the initial study group and only 2 bottles of 20% in the second study group. This lead to a cost saving, on average of £57.06 per paracentesis, this becomes substantial when added to the cost savings of day case versus overnight stay. There were no clinically significant changes in renal function or haemodynamic parameters in either data set. 86% of patients initially studied had a UKELD score greater than 49 with a median value of 54.5 (range 4–0). There were 7 repeat attenders in the initial group and 4 in the second, attending 3 and 4 weekly, respectively. Only one patient was studied in both data sets with increased drain frequency from monthly to fortnightly. Conclusions: Both data sets have shown variability of ascitic fluid volume and drainage rates. We must continue an individualised approach to refractory ascites, but changes to our standard operating procedure have increased elective paracentesis capacity by 74%, reduced pressure on unplanned care and reduced costs by £793.06 per paracentesis. The changes are safe with no clinically significant renal function or haemodynamic deterioration. It is difficult to attribute cause to changes in paracentesis frequency given the multiple confounding factors related to ascites production.